PERHITUNGAN DAYA DUKUNG PONDASI DANGKAL JENIS MENERUS DENGAN BERBAGAI METODE - Putra, Firgi Ikko Gustianto (Jurnal Vokasi Teknik Sipil, 2023)
Continuous foundation is one type of foundation that is often used in building construction. This foundation is usually used for buildings that are not too heavy, such as residential houses or other small buildings. As the name implies, the foundation is continuous and elongated or commonly called the path foundation. Continuous foundations consist of several types, including river stone foundations and brick / roll foundations. Kali stone foundations use large stones as the base and foundation walls. While the brick / rollag foundation is made of piles of bricks assembled with concrete mortar. The purpose of the study is to analyze the continuous foundation planning in accordance with technical standards and regulations applicable in the construction of the continuous foundation in Indonesia and understand the concept of the continuous foundation itself, as well as to understand the continuous foundation planning in Indonesia. In this study, the subject of research is literature related to continuous foundation planning. The results of this study found that continuous foundation planning has the aim of knowing the carrying capacity of the soil and ensuring the safety and stability of the building in order to reduce the risk of damage and failure of buildings in the future. The methods used in this research are qualitative descriptive methods and literature studies through reviewing journals and books on the internet and print media regarding continuous foundation planning and soil carrying capacity investigation